The Level of Knowledge of Kancil Mas U-21 Football Athletes about Sports Injuries, Treatment, and Prevention - Setiawan, M. Arief; Aulia, Dany; Kaffah, Syfah Nur; Yusuf, Achmad Humaedi; Kharis, Muhammad Candra (Universitas Negeri Semarang, 2024)
Abstract. The study aims to determine the level of knowledge among Kancil Mas football athletes regarding sports injuries, treatment, and prevention. A descriptive statistical design is employed to obtain an overview of athletes’ understanding of injury management in sports contexts. Data collection was carried out using an online questionnaire distributed through Google Forms via the WhatsApp application. The sample consisted of thirteen male Kancil Mas football athletes aged between nineteen and twenty-one years. The research findings revealed that a considerable proportion of athletes demonstrated a moderate to low level of understanding related to sports injuries, as well as methods for treatment and prevention. The outcome indicates that Kancil Mas football athletes generally possess a moderate level of knowledge in recognizing, managing, and preventing sports injuries, emphasizing the importance of continuous education and injury-prevention training in athlete development programs. Abstrak. Penelitian ini bertujuan untuk mengetahui tingkat pengetahuan atlet sepak bola Kancil Mas mengenai cedera olahraga, penanganan, dan pencegahannya. Penelitian ini menggunakan pendekatan deskriptif dengan analisis statistik sederhana. Pengumpulan data dilakukan melalui penyebaran angket atau kuesioner secara daring menggunakan Google Form melalui aplikasi WhatsApp. Sampel penelitian terdiri atas 13 atlet sepak bola Kancil Mas berjenis kelamin laki-laki dengan rentang usia 19–21 tahun. Hasil penelitian menunjukkan bahwa sebagian besar atlet sepak bola Kancil Mas memiliki tingkat pemahaman yang masih tergolong sedang bahkan rendah mengenai cedera olahraga, serta penanganan dan pencegahannya. Berdasarkan hasil tersebut dapat disimpulkan bahwa atlet sepak bola Kancil Mas memiliki tingkat pengetahuan sedang tentang cedera olahraga serta cara penanganan dan pencegahannya.